2002
DOI: 10.1110/ps.2500102
|View full text |Cite
|
Sign up to set email alerts
|

Classification of G‐protein coupled receptors by alignment‐independent extraction of principal chemical properties of primary amino acid sequences

Abstract: We have developed an alignment-independent method for classification of G-protein coupled receptors (GPCRs) according to the principal chemical properties of their amino acid sequences. The method relies on a multivariate approach where the primary amino acid sequences are translated into vectors based on the principal physicochemical properties of the amino acids and transformation of the data into a uniform matrix by applying a modified autocross-covariance transform. The application of principal component a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 22 publications
2
78
0
Order By: Relevance
“…Huang 64 recently published that the TM3 helix position (3.32) and the TM7 helix position (7.40) are sufficient for classifying the aminergic GPCRs and for predicting novel members of this class among orphan GPCR sequences. Prusis et al [66][67][68][69] reported a proteochemometrics approach to identify amino acid motifs important for ligand binding to aminergic GPCR receptors from within the TM regions. They described the aligned 7TM helices of the aminergic GPCRs by physicochemical descriptors and applied a multivariate analysis to explore the interactions of the TM helix amino acids of the R 1a -, R 1b -, and R 1d -adrenoreceptors with 4-piperidyl oxazole antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Huang 64 recently published that the TM3 helix position (3.32) and the TM7 helix position (7.40) are sufficient for classifying the aminergic GPCRs and for predicting novel members of this class among orphan GPCR sequences. Prusis et al [66][67][68][69] reported a proteochemometrics approach to identify amino acid motifs important for ligand binding to aminergic GPCR receptors from within the TM regions. They described the aligned 7TM helices of the aminergic GPCRs by physicochemical descriptors and applied a multivariate analysis to explore the interactions of the TM helix amino acids of the R 1a -, R 1b -, and R 1d -adrenoreceptors with 4-piperidyl oxazole antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, some rely on transformations based on the amino acid physicochemical characteristics, such as the ACC transformation [22,41] and the mean transformation [26]. Some advantages of these representations are that: a) they can help to discover divergent receptor genes [20]; b) they do not require a homologous relationship among similar sequences to be assumed; and c) their transformed output can directly be used by standard pattern recognition and machine learning methods.…”
Section: Alignment-free Gpcr Representationsmentioning
confidence: 99%
“…In the current study, we use several of them to transform the data sequences, including the Auto-Cross Covariance (ACC) transform [22] and the physicochemical distance transformation (PDT: [23]). In a less complex procedure described in [10] and [26], each GPCR is represented using the means of five z-scale physicochemical descriptors over the sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Given that this receptor does not have a close homolog, the chemical nature of such a ligand is difficult to infer. Accordingly, EBI2 has been placed in varying 7TM receptor subgroups by different phylogenetic analyses as being a target of peptide (1,5) or lipid ligands (6). Nevertheless, many aspects of EBI2 signaling have been revealed.…”
mentioning
confidence: 99%